The Gross Motor Skill Differences Between Preschool Boys and Girl - Arifiyanti, Nurul (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2020)
Every stage in human development has different phase. Not only in every stage but also in gender, motor skill has their own characteristics. Moreover, there is a question of the validity and reliability of some tests used by the researcher. The study was conducted in Purworejo, Jawa Tengah, Indonesia. A total of 82 children enrolled in this study, including 12 children aged between 3-4 years, 36 children aged between 4 and 5 years, and 34 children aged between 5 and 6 years. The test of gross motor development-second (TGMD-2) edition was used to evaluate gross motor skill. Independent T-test was used to analyzed the final result. The findings of this study demonstrated that the boys have higher gross motor skills performance than the girls. The school can use this fact to plan curriculum that not based in gender. School must be a campaign system for gender equality